Push-Pull-Triacetylene und Push-Pull-Tetraacetylene - Urs Stämpfli; Markus Neuenschwander (CHIMIA)
The first synthesis of push-pull-triacetylenes of type 3 as well as of push-pull-tetraacetylenes of type 4 is described (Scheme 2). Perchlorobutenyne 5 is reacted with the lithium-ynamine 6a and the lithium-diynamine 7b respectively. Dechlorination of 8a and 9b by means of two equivalents of n-butyllithium and subsequent acylation gives the triacetylene 3a and tetraacetylene 4b in so far rather moderate yields.